Gata4 expression in lateral mesoderm is downstream of BMP4 and is activated directly by Forkhead and GATA transcription factors through a distal enhancer element. - Rojas, A; De Val, S; Heidt, AB; Xu, S; Bristow, J; Black, B (2005)
The GATA family of zinc-finger transcription factors plays key roles in the specification and differentiation of multiple cell types during development. GATA4 is an early regulator of gene expression during the development of endoderm and mesoderm, and genetic studies in mice have demonstrated that GATA4 is required for embryonic development. Despite the importance of GATA4 in tissue specification and differentiation, the mechanisms by which Gata4 expression is activated and the transcription factor pathways upstream of GATA4 remain largely undefined. To identify transcriptional regulators of Gata4 in the mouse, we screened conserved noncoding sequences from the mouse Gata4 gene for enhancer activity in transgenic embryos. Here, we define the regulation of a distal enhancer element from Gata4 that is sufficient to direct expression throughout the lateral mesoderm, beginning at 7.5 days of mouse embryonic development. The activity of this enhancer is initially broad but eventually becomes restricted to the mesenchyme surrounding the liver. We demonstrate that the function of this enhancer in transgenic embryos is dependent upon highly conserved Forkhead and GATA transcription factor binding sites, which are bound by FOXF1 and GATA4, respectively. Furthermore, the activity of the Gata4 lateral mesoderm enhancer is attenuated by the BMP antagonist Noggin, and the enhancer is not activated in Bmp4-null embryos. Thus, these studies establish that Gata4 is a direct transcriptional target of Forkhead and GATA transcription factors in the lateral mesoderm, and demonstrate that Gata4 lateral mesoderm enhancer activation requires BMP4, supporting a model in which GATA4 serves as a downstream effector of BMP signaling in the lateral mesoderm.